Pulse quality analysis on soliton pulse compression and soliton self-frequency shift in a hollow-core photonic bandgap fiber - González Baquedano, N.; Torres Gómez, Ismael; Arzate, N.; Ferrando, A.; Ceballos Herrera, Daniel E. (2013)
A numerical investigation of low-order soliton evolution in a proposed seven-cell hollow-core photonic bandgap fiber is reported. In the numerical simulation, we analyze the pulse quality evolution in soliton pulse compression and soliton self-frequency shift in three fiber structures with different cross-section sizes. In the simulation, we consider unchirped soliton pulses (of 400 fs) at the wavelength of 1060 nm. Our numerical results show that the seven-cell hollow-core photonic crystal fiber, with a cross-section size reduction of 2%, promotes the pulse quality on the soliton pulse compression and soliton self-frequency shift. For an input soliton pulse of order 3 (which corresponds to an energy of 1.69 μJ), the pulse gets compressed with a factor of up to 5.5 and a quality factor of 0.73, in a distance of 12 cm. It also experiences a soliton-self frequency shift of up to 28 nm, in a propagation length of 6 m, with a pulse shape quality of ≈ 0.80.